1983
DOI: 10.1007/bf00140269
|View full text |Cite
|
Sign up to set email alerts
|

The professional development of Australian university teachers: An act of faith?

Abstract: Teaching is the major professional activity of academic staff in Australian universities. Much disquiet about the quality of this teaching has been expressed by governments, committees of enquiry, students and by academics. There have been several attempts to improve the quality of university teaching, all of which have been considerable acts of faith. The persistence of disquiet, however, suggests that past efforts to improve the quality of university teaching have not been completely successful.An analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…These are perennial problems in staff training and development (Brown, 1977;Wergin, 1977;Hewton, 1979;Teather, 1979;Cannon, 1983). The clues, if not the solution, lie in the suggestions offered by the respondents themselves.…”
Section: Recommended Guidelines and Strategiesmentioning
confidence: 96%
“…These are perennial problems in staff training and development (Brown, 1977;Wergin, 1977;Hewton, 1979;Teather, 1979;Cannon, 1983). The clues, if not the solution, lie in the suggestions offered by the respondents themselves.…”
Section: Recommended Guidelines and Strategiesmentioning
confidence: 96%
“…Cannon (1983) has suggested that herein may lie one explanation for the apparent failure of teaching improvement initiatives in Australian universities. Typically such initiatives have focussed on developing the individual in the hope that the 'good' word would spread.…”
Section: The Findings and Their Implicationsmentioning
confidence: 94%
“…Faculty members, besides belonging to their own organizations, also owe allegiance to other disciplinary colleagues, often feeling the later loyalty stronger than the institutional one (Cannon, 1983). Therefore, besides the evidence that might point towards a common perception of culture, faculty members also respond to two main sources of variation:…”
Section: Impact Of Organizational and Individual Variables On Job Satmentioning
confidence: 99%